Harmonisasi Sosial Melalui Pendekatan Religi: Respons Kemanusiaan Bagi Masyarakat Terdampak Letusan Gunung Semeru - Wilopo; Abdullah Said; Benny Hutahayan; Nuralam, Inggang Perwangsa; Rizal Alfisyahr (Future Science, 2023)
Indonesia, known for its geological richness, often experiences natural disasters. One such event was the eruption of Mount Semeru in December 2021 in Lumajang Regency, East Java. The incident posed complex recovery challenges. According to the National Disaster Management Agency (BNPB) report, infrastructure damage reached billions of rupiahs, and thousands of residents were displaced. The challenges extended beyond infrastructure recovery, encompassing the psychological recovery of traumatized residents. Disruptions to the local economy, family separations, and other losses exacerbated the psychosocial burden faced by the affected population. The communities impacted by the eruption of Mount Semeru faced diverse challenges, particularly in religious aspects and the fulfillment of funeral rites (Rukun Kematian). This study highlights the importance of meeting funeral rites needs at every Social Facility (Fasilitas Sosial or Fasos) as a primary foundation for post-disaster recovery. Through collaboration with BNPB, the Social Assistance Program has successfully allocated resources for meeting these needs. Surveys of each Fasos revealed their specific requirements, ranging from funeral equipment to loudspeakers. Technical assistance related to funeral rites was provided by competent practitioners. Although it has shown positive impacts, this research emphasizes the sustainability of assistance as a key factor in the long-term recovery of the affected community. As a recommendation, this assistance should continue, considering the dynamics and changing needs of the community, to ensure ongoing optimal support in facing post-disaster challenges.